2020
DOI: 10.1101/2020.02.09.940320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Prototyping of Wireframe Scaffolded DNA Origami using ATHENA

Abstract: Wireframe DNA origami assemblies can now be programmed automatically from the "top-down" using simple wireframe target geometries, or meshes, in 2D and 3D geometries using either rigid, six-helix bundle (6HB) or more compliant, two-helix bundle (2HB or DX) edges. While these assemblies have numerous applications in nanoscale materials fabrication due to their nanoscale spatial addressability and high degree of customization, no easy-to-use graphical user interface software yet exists to deploy these algorithmi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recently, two new software have been reported that enhance the capabilities of DNA origami design by combining features from the 1G and 2G software. ATHENA 51 integrates features of other existing 2G software, specifically that of DAEDALUS, PERDIX, TALOS and METIS. Adenita 52 is an open source platform that combines almost all of the 1G and 2G design software capabilities.…”
Section: Experimentationmentioning
confidence: 99%
“…Recently, two new software have been reported that enhance the capabilities of DNA origami design by combining features from the 1G and 2G software. ATHENA 51 integrates features of other existing 2G software, specifically that of DAEDALUS, PERDIX, TALOS and METIS. Adenita 52 is an open source platform that combines almost all of the 1G and 2G design software capabilities.…”
Section: Experimentationmentioning
confidence: 99%
“…All of the described solutions have recently been incorporated into one platform, called ATHENA [ 48 ]. It provides the user with an intuitive GUI, which drastically increases the easy usability of each of the previous algorithms, so that any wireframe DNA origami in two- or three dimensions using either 2 HB or 6 HB edges can be created.…”
Section: Scaffolded Dna Origamimentioning
confidence: 99%
“…Published by Springer Nature Ltd., 2019. (g) reproduced with permission from [84]. Copyright by the authors of [84], 2020.…”
Section: Automatic Top-down Fabrication With Daedalus Perdix Talosmentioning
confidence: 99%
“…All these distinct algorithms are embedded in a software package ATHENA [84,85] that has an intuitive graphical interface, thus allowing the user to design any kind of 2D or 3D wireframe structure with 2HB or 6HB edges (Figure 4g). The scaffold routing and staple sequences are defined automatically for the target shape, and importantly, external editing of sequences using most commonly employed caDNAno software [14,15] is enabled in the workflow.…”
Section: Automatic Top-down Fabrication With Daedalus Perdix Talosmentioning
confidence: 99%
See 1 more Smart Citation